Exploration of the minimum visual disability criteria for Para nordic and Para alpine skiing using simulated vision impairments. (13th August 2021) - Stalin, Amritha; Dalton, Kristine
ABSTRACT: The International Paralympic Committee Classification Code requires sports to develop evidence-based, sports-specific classification systems. This project aimed to determine the minimum eligibility criteria for Para nordic and Para alpine skiing by simulating vision impairments and measuring the impact of the impairments on performance in twenty-two nordic (28.09 ± 9.68 years; 16 male) and eleven alpine (37.91 ± 18.9 years, 11 male) able-sighted skiers. Eight visual acuity (VA)/contrast sensitivity (CS) (Cambridge Simulation Glasses, University of Cambridge) and six visual field (VF) impairments (bespoke goggles; University of Waterloo) were simulated. VA, CS and VF were measured in each participant before they completed an on-snow session, skiing short competition-style courses with each of the 14 simulated impairments in a randomized order. Clear goggle (no impairment) trials were used as controls. Receiver Operating Characteristic (ROC) and decision tree analyses were conducted to determine the optimum VA, CS and VF cut-offs for classifying performance based on differences from baseline in real time. Moderate impairments in VA, CS and VF negatively affect skiing performance. The recommended cut-off criteria based on both analyses were VA ≥0.90 logMAR and ≤48% VF extent for nordic and VA of ≥0.60 logMAR and VF extent of ≤59.0% for alpine.